2016
DOI: 10.1007/s11771-016-0375-6
|View full text |Cite
|
Sign up to set email alerts
|

Galerkin solution of Winkler foundation-based irregular Kirchhoff plate model and its application in crown pillar optimization

Abstract: Irregular plates are very common structures in engineering, such as ore structures in mining. In this work, the Galerkin solution to the problem of a Kirchhoff plate lying on the Winkler foundation with two edges simply supported and the other two clamped supported is derived. Coordinate transformation technique is used during the solving process so that the solution is suitable to irregular shaped plates. The mechanical model and the solution proposed are then used to model the crown pillars between two adjac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Domestic and foreign scholars have carried out a lot of experimental research on the mechanical properties of tailings sand. Peng et al 7 took the damming tailings of Xiaoda’e tailings pond as the research object, and carried out a comparative study of dynamic triaxial tests on two kinds of tailings, namely tailing silt sand and tailing silt soil. The results showed that the dynamic strength and dynamic elastic modulus of tailing silt soil were significantly lower than those of tailing silt sand.…”
Section: Introductionmentioning
confidence: 99%
“…Domestic and foreign scholars have carried out a lot of experimental research on the mechanical properties of tailings sand. Peng et al 7 took the damming tailings of Xiaoda’e tailings pond as the research object, and carried out a comparative study of dynamic triaxial tests on two kinds of tailings, namely tailing silt sand and tailing silt soil. The results showed that the dynamic strength and dynamic elastic modulus of tailing silt soil were significantly lower than those of tailing silt sand.…”
Section: Introductionmentioning
confidence: 99%
“…The hypothesis of the beam is widely used, including cantilever beam theory [21,22], masonry beam theory [23,24], transfer rock beam theory [25,26], and elastic foundation beam theory [27,28]. The plate hypothesis mainly includes the thin plate theory [29,30] and the Kirchhoff plate theory [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…ey are the basic components in structures such as roads, bridges, and high-rise building foundations. It is critical to apply structural components in engineering practice reasonably and safely, and these concerns have attracted the attention of various academic and engineering circles [1][2][3]. To study the practical issues related to elastic foundation beams, many models of beams on elastic foundations have been proposed by scholars.…”
Section: Introductionmentioning
confidence: 99%